Prognostic impact of early‐versus‐late responses to different induction regimens in patients with myeloma undergoing autologous hematopoietic cell transplantation: Results from the CALM study by the CMWP of the EBMT. (27th February 2021) - Garderet, Laurent; Sbianchi, Giulia; Iacobelli, Simona; Blaise, Didier; Byrne, Jenny L.; Remenyi, Peter; Apperley, Jane F.; Touzeau, Cyrille; Isaksson, Cecilia; Browne, Paul; Mayer, Jiri; Lenhoff, Stig; et al.
Abstract: Background: In autologous stem cell transplant (ASCT)‐eligible myeloma patients, prolonged induction does not necessarily improve the depth of response. Method: We analyzed 1222 ASCT patients who were classified based on (a) the interval between induction and stem cell collection, (b) the type of induction regimen: BID (Bortezomib, IMiDs, and Dexamethasone), Bortezomib‐based, or CTD (Cyclophosphamide, Thalidomide, and Dexamethasone), and (c) the time to best response (Early ie, best response within 4 or 5 months, depending on the regimen vs Late; Good ie, VGPR or better vs Poor). Results: The length of induction treatment required to achieve a Good response did not affect PFS ( P = .65) or OS ( P = .61) post‐ASCT. The three types of regimen resulted in similar outcomes: median PFS 31, 27.7 and 30.8 months ( P = .31), and median OS 81.7, 92.7, and 77.4 months, respectively ( P = .83). On multivariate analysis, neither the type nor the duration of the induction regimen affected OS and PFS, except for Early Good Responders who had a better PFS compared to Early Poor Responders (HR = 1.21, P ‐value = .02). However, achieving a Good response at induction was associated with a better response (≥VGPR) post‐transplant. Conclusion: The kinetics of response did not affect outcomes.